Comparative analysis of transient valve-induced flow characteristics between opening and closing processes. (August 2022) - Liu, Qi; Tian, Shuai; Wang, Yong-xiang; Lin, Zhe; Zhu, Zu-chao
Transient control of process valves, including opening and closing processes, is consistently encountered in many fluid transportation and control industries. During opening and closing processes, valve-induced transient flow presents different unstable flow characteristics. This transient valve-induced unstable flow that develops along the pipeline can cause violent pressure and velocity fluctuations that considerably influence accurate flow measurement downstream. In this paper, gate valve-induced flow characteristics during opening and closing processes were comparatively studied. An experimental system was developed to monitor the downstream pressure along the pipeline, and corresponding transient numerical simulations were performed on opening and closing processes using a user-defined function and dynamic grid technology. The pressure distributions along the pipeline's downstream area during valve opening and closing processes were investigated to verify the accuracy of the numerical simulation. The mechanism of transient flow difference under the same valve opening during opening and closing processes was determined to be a hysteresis effect. The jet flow intensity under a small valve opening in the opening process was greater than that in the closing process, and the difference in flow field under the 50% valve opening was the largest. Moreover, the velocity and turbulent kinetic energy distributions in different downstream cross-sections during valve opening and closing processes were comparatively analyzed. The change rate of the maximum turbulent kinetic energy was introduced to further analyze the different effects of opening and closing processes on the transient flow stability downstream of the valve. Results showed that the flow stability between 40% and 50% valve opening was the worst irrespective of the adjustment process, that is, a large pipeline distance was required to stabilize this transient flow. This study helps in understanding transient valve-induced flow characteristics in fluid transportation pipelines and provides guidance for accurate flow metering industrial applications.